2018
DOI: 10.2196/publichealth.8953
|View full text |Cite
|
Sign up to set email alerts
|

The SMART Study, a Mobile Health and Citizen Science Methodological Platform for Active Living Surveillance, Integrated Knowledge Translation, and Policy Interventions: Longitudinal Study

Abstract: BackgroundPhysical inactivity is the fourth leading cause of death worldwide, costing approximately US $67.5 billion per year to health care systems. To curb the physical inactivity pandemic, it is time to move beyond traditional approaches and engage citizens by repurposing sedentary behavior (SB)–enabling ubiquitous tools (eg, smartphones).ObjectiveThe primary objective of the Saskatchewan, let’s move and map our activity (SMART) Study was to develop a mobile and citizen science methodological platform for a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(89 citation statements)
references
References 67 publications
0
81
0
1
Order By: Relevance
“…Smartphones have been used to improve disease surveillance in areas such as cardiovascular disease, oral cancer and tuberculosis. 18,19 Mobile technology not only improves data collection but also allows timely access to the information. 10 Furthermore, the World Health Organization (WHO) has recently released a statement about the use of appropriate digital technologies for public health, which explicitly highlights the potential to obtain information directly from the public to support disease surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…Smartphones have been used to improve disease surveillance in areas such as cardiovascular disease, oral cancer and tuberculosis. 18,19 Mobile technology not only improves data collection but also allows timely access to the information. 10 Furthermore, the World Health Organization (WHO) has recently released a statement about the use of appropriate digital technologies for public health, which explicitly highlights the potential to obtain information directly from the public to support disease surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…These studies bring together individuals in communities with environmental public health issues to make observations and clarify regional perspectives. Katapally et al (2018) reported on a recent study using a mobile app to collect information on physical activity, physical and social context, and motivation and tested information interventions to increase active living behaviors. In epidemiology, citizen science approaches have been used to enable the public to actively participate in health surveillance (Deepwater Horizon spill, Sullivan et al (2018)) or in observing environmental changes.…”
Section: Advances Using Citizen Science and Smartphone Approachesmentioning
confidence: 99%
“…New citizen scientists and crowdsourcing research efforts have successfully capitalized on the power of smartphones to engage users when the information is most relevant. Katapally et al (2018) reported on a recent study using a mobile app to collect information on physical activity, physical and social context, and motivation and tested information interventions to increase active living behaviors. Chrisinger and King (2018) engaged citizen scientists to report objective and perceived elements of the built environment that contribute to chronic stress.…”
Section: Advances Using Citizen Science and Smartphone Approachesmentioning
confidence: 99%
“…Analogous to the movement in other realms of citizen science, there is a growing movement toward more participant/patient involvement in research on humans, including in elds such as radiology, public health, psychology, and epidemiology [59,60]. Patients often have a better understanding of their disease and needs than medical/research professionals [61,62] and that patient involvement can help catalyze policy interventions [63]. Examples include the studies on amyotrophic lateral sclerosis initiated by PatientsLikeMe users [64], crowd-sourcing e orts like American Gut [65], and a variety of other citizen genomics e orts [66].…”
Section: Participant Involvementmentioning
confidence: 99%